Переваги систем електричного опалення з нічним акумулюванням теплоти в умовах України - Андрющенко, А.М.; Нікульшин, В.Р.; Денисова, А.Є. (Електротехніка і електромеханіка, 2018)
Мета. Мета дослідження - розробка системи електричного опалення з нічним акумулюванням теплоти та обґрунтування її енергозберігаючого характеру в порівнянні з іншими можливими варіантами опалення. Методика. Методика заснована на сучасних стандартах України і включає наступні основні допущення: коефіцієнт корисної дії електричного котла приймається рівним 100 %; залежність опалювального навантаження будівлі від зовнішньої температури вважається лінійною; для всіх розрахункових варіантів опалення, що використовують різні енергетичні ресурси, режим роботи системи опалення відстежує погодні умови відповідно до температури зовнішнього повітря. Методика передбачає визначення основних технічних характеристик системи з урахуванням можливості включення електричного бойлера в денний час на половину розрахункового навантаження. Результати. На основі запропонованого методу була розроблена розрахункова програма для визначення щомісячного теплоспоживання будівлі і розрахунку вартості опалення при використанні різних енергетичних ресурсів. Ця програма також дозволяє зіставляти вартості централізованого теплопостачання як по теплоті, що спожита, так і при оплаті за величиною опалювальної площі. Наукова новизна. Вперше наведені метод і програма розрахунку систем електроопалення з нічним акумулюванням теплоти, що враховують діючі стандарти України та дозволяють визначати основні технічні характеристики системи, а також розраховувати вартості опалення при використанні різних видів енергетичних ресурсів. Практичне значення. Використання запропонованої методики дозволяє проектувати енергозберігаючі системи електричного опалення з нічним акумулюванням теплоти. Наведено чисельний приклад для реальних погодних умов м. Києва. Доведено, що термін окупності переходу на електроопалення для варіанту заміни централізованого теплопостачання з оплатою за спожиту теплоту складає менше, ніж 3 роки, для варіанту заміни централізованого теплопостачання з оплатою за опалювальну площу складає менш, ніж 1 рік. Цель. Цель исследования - разработка системы электрического отопления с ночным аккумулированием теплоты и обоснование ее энергосберегающего характера по сравнению с другими возможными вариантами отопления. Методика. Методика основана на современных стандартах Украины и включает следующие основные допущения: коэффициент полезного действия электрического котла принимается равным 100 %; зависимость отопительной нагрузки здания от внешней температуры считается линейной; для всех расчетных вариантов отопления, использующих различные энергетические ресурсы, режим работы системы отопления отслеживает погодные условия в соответствии с температурой наружного воздуха. Методика предусматривает определение основных технических характеристик системы с учетом возможности включения электрического бойлера в дневное время на половину расчетной нагрузки. Результаты. На основе предложенного метода была разработана расчетная программа для определения ежемесячного теплопотребления здания и расчета стоимости отопления при использовании различных энергетических ресурсов. Эта программа также позволяет сопоставлять стоимости централизованного теплоснабжения как по потребленной теплоте, так и при оплате по величине отапливаемой площади. Научная новизна. Впервые приведены метод и программа расчета систем электроотопления с ночным аккумулированием теплоты, учитывающие действующие стандарты Украины и позволяющие определять основные технические характеристики системы, а также рассчитывать стоимости отопления при использовании различных видов энергетических ресурсов. Практическое значение. Использование предлагаемой методики позволяет проектировать энергосберегающие системы электрического отопления с ночным аккумулированием теплоты. Приведен численный пример для реальных погодных условий г. Киева. Показано, что срок окупаемости перехода на электроотопление для варианта замены централизованного теплоснабжения с оплатой за потребленную теплоту составляет менее 3 лет, для варианта замены централизованного теплоснабжения с оплатой за отапливаемую площадь составляет менее 1 года Purpose. To develop electrical heating systems with night heat accumulation and to prove its advantages comparable with others possible variants of heating. Methodology. We have purposed a methodology which is based on the current Standards of Ukraine and included few main assumptions: the efficiency of the electric boiler is assumed equal 100 %; the dependence of the building heating load on the outside temperature is linear; all the variants of different energy resources calculating for the system operating correspond to the adequate (depending on weather) regulation. Methodology allows to determine the main technical characteristics of the system taking into account the possibility of switching on the electric boiler in the daytime using the half-loading. On the base of suggested methodology was developed the calculation program for determine the monthly consumption of heat by the building and estimate the cost of heating using different energy sources. This program also allows to compare the payment for centralized heat supply services at the tariff for the consumed heat with a payment for the heated area tariff. Results. We have obtained a method for electrical heating systems with night heat accumulation calculation. Method bases on the current Standards in Ukraine and allows to determine the main technical characteristics of the system taking into account the possibility of switching on the electric boiler in the daytime. On the base of suggested method was developed the calculation program for determine the monthly consumption of heat by the building and estimate the cost of heating using different energy resources. This program also allows to compare the payment for centralized heat supply services at the tariff for the consumed heat with a payment for the heated area tariff. Originality. For the first time we have suggested methodology and developed the calculation program for electrical heating systems with night heat accumulation which is based on the Ukrainian Standards and allows to determine the monthly consumption of heat by the building and estimate the cost of heating using different energy sources. Practical value. We have developed a method and calculation program which allows to design the energy saving electrical heating systems with night heat accumulation. We have demonstrated on the numerical example for the real weather conditions of Kyiv city the economical advance of using electric heating with night heat accumulation comparable with all others options (centralized heat supply, gas heating, pellet heating). For December 2017 tariffs in Ukraine, the cost of electrical heating with night heat accumulation are two times lower than in the case of centralized heat supply with payment for consumed heat. We have proved that the refund period for implementation of electrical heating systems with night heat accumulation instead of centralized heat supply services at the tariff for the consumed heat is less than 3 years, and for centralized heat supply services at the tariff for the heated area tariff is less than 1 year.